Hotspots of biogeochemical activity linked to aridity and plant traits across global drylands - Eldridge, David J. (2024)
Fil: Centre for Ecosystem Science, School of Biological, Earth and Environmental Sciences, University of New South Wales, Sydney, New South Wales, Australia.